2005
DOI: 10.1136/inpract.27.8.418
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and management of cardiovascular disease in rabbits

Abstract: ANECDOTAL reports from veterinary surgeons suggest that cardiovascular disease is increasingly being diagnosed in rabbits. With the rise in popularity of this species as a pet, and often a house pet, owners are noticing subtle signs of disease and are presenting their animals for investigation at an earlier stage. This article describes how a systematic approach to the investigation can lead to improved management and, hence, a better outlook for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 12 publications
2
18
0
5
Order By: Relevance
“…The animals studied had the same electrical axis measurement as that presented by non-anesthetized agouti (-160 to 180°) (Diniz et al 2013), and there was little variation in the syntopic relationship between the heart and the thoracic cavity, reaffirming the morphological aspect of the thoracic cavity of this species. The values of the electric axis for agoutis are closer to those found for rabbits (Reusch 2005, Lord et al 2010) than those reported for cats (Tilley 1992), even though the latter species is similar in size to the animals studied. As a result, we can understand that the relation of the heart size to the thorax directly influences the heart axis of each species (and even each breed within the same species, as reported for dogs by Tilley (1992)); therefore, specific studies are needed to determine the standard for each species.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The animals studied had the same electrical axis measurement as that presented by non-anesthetized agouti (-160 to 180°) (Diniz et al 2013), and there was little variation in the syntopic relationship between the heart and the thoracic cavity, reaffirming the morphological aspect of the thoracic cavity of this species. The values of the electric axis for agoutis are closer to those found for rabbits (Reusch 2005, Lord et al 2010) than those reported for cats (Tilley 1992), even though the latter species is similar in size to the animals studied. As a result, we can understand that the relation of the heart size to the thorax directly influences the heart axis of each species (and even each breed within the same species, as reported for dogs by Tilley (1992)); therefore, specific studies are needed to determine the standard for each species.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study however, the positioning of the animals was the same for all the individuals, suggesting differences in the P wave amplitude. In rabbits that were given an electrocardiogram, the P wave showed different morphology in some breeds, but without any pathological significance (Reusch 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, foi escolhida a de Teicholz, por se assemelhar mais às mensurações invasivas e apresentar maior correlação nas mensurações em gatos. Stypmann et al (2007) Não foi observada depressão cardiorrespiratória nem no G1 (maleato de midazolam mais cloridrato de cetamina)  o que corrobora com Dupras et al (2001), que alega ser esta mínima  nem no G2 (maleato de midazolam), estando de acordo com Reusch (2005).…”
Section: Methodsunclassified
“…Para avaliar estes efeitos, foram escolhidos dois protolocos anestésico-sedativos que promovem imobilização adequada e em tempo hábil para o procedimento ecoDopplercardiográfico e comparou-se um protocolo recentemente utilizado: midazolam associado ao cloridrato de cetamina (Fontes-Sousa et al, 2009) com a utilização apenas do midazolam, ainda não utilizado em pesquisas ecoDopplercardiográficas em coelhos, com a justificativa de este último promover boa sedação e causar menos efeitos cardiovasculares em doses que variam de 0,5 a 1,0mg/kg por via intramuscular (IM) (Reusch, 2005).…”
unclassified
“…In rabbits submitted to electrocardiography, there were morphologically different P waves in some breeds, but with no pathological significance [39].…”
Section: Discussionmentioning
confidence: 99%